2021
DOI: 10.3390/nano11112984
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Growth of 36 Inner Nanotubes inside Nickelocene, Cobaltocene and Ferrocene-Filled Single-Walled Carbon Nanotubes

Abstract: We have investigated the effects of temperature, diameter and metal catalyst type on the growth of inner nanotubes inside metallocene-filled single-walled carbon nanotubes (SWCNTs). The effects on the yield of different chiralities of inner nanotubes were scrutinized by multifrequency Raman spectroscopy. The investigated diameters range from ~0.7 to 1.3 nm and comprise 36 distinct chiralities. For all three investigated metals (Ni, Co, Fe), there is a linear correlation of growth temperature with nanotube diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Raman spectroscopy is nondestructive method of investigation of the electronic properties of SWCNTs. The shifts of bands and their modifications are analyzed, and modification of the electronic properties is studied [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 42 , 43 , 44 , 46 , 47 , 49 , 50 , 51 , 55 , 56 , 57 , 61 , 62 , 63 , 64 , 65 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Remarks On Characterization Methods Of Filled Swcntsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman spectroscopy is nondestructive method of investigation of the electronic properties of SWCNTs. The shifts of bands and their modifications are analyzed, and modification of the electronic properties is studied [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 42 , 43 , 44 , 46 , 47 , 49 , 50 , 51 , 55 , 56 , 57 , 61 , 62 , 63 , 64 , 65 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Remarks On Characterization Methods Of Filled Swcntsmentioning
confidence: 99%
“…It is found that different fillers lead to changes in electronic structure of nanotubes with n- or p-doping. The insertion of metal halogenides, metal chalcogenides, metallocenes, and metals leads to the Fermi level shift of −0.3–0.4 eV, −0.3 eV, +0.05–0.1 eV, and +0.3 eV [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 42 , 43 , 44 , 46 , 47 , 49 , 50 , 51 , 55 , 56 , 57 , 61 , 62 , 63 , 64 , 65 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. The encapsulation of rubidium iodide leads to the Fermi level shift of +0.2 eV, i.e., donor doping [ 47 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a large field of work on chemically functionalized carbon nanotubes. It was shown that metal halogenide-filled SWCNTs with a decreased [ 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 ] Fermi level, metal chalcogenide-filled SWCNTs [ 161 , 162 , 163 ], metal-filled SWCNTs [ 164 , 165 , 166 ], metal halogenide-filled SWCNTs [ 167 ], and metallocene-filled SWCNTs [ 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 ] with an increased Fermi level can be used for the electrochemical measurements.…”
Section: Investigations Of Chemically Functionalized Carbon Nanotubesmentioning
confidence: 99%
“…Raman spectroscopy is used to identify the charge transfer and electronic and vibronic properties of filled SWCNTs [ 181 , 182 , 183 , 184 , 185 ]. Figure 18 shows the Raman spectra of pristine and cobalt iodide-filled SWCNTs obtained at different laser wavelengths [ 238 ].…”
Section: Investigations Of Chemically Functionalized Carbon Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation